Das Unternehmen Kunst. (Köln : Kulturkreis der deutschen Wirtschaft im Bundesverband der Deutschen Industrie e.V., 1998)
Demand, Thomas ; Kricke, Norbert ; Uecker, Günther ; Antes, Horst ; Nay, Ernst Wilhelm ; Baumeister, Willi ; Grieshaber, HAP ; Geiger, Rupprecht ; Tillmans, Wolfgang ; van Ofen, Michael ; Huber, Thomas ; Terfloth, Beate ; Weiss-Leder, Ute
bibliografie
Duits
boek